Assessment of soft and hard tissue dimensions following different treatment approaches of ligature‐induced peri‐implantitis defects. Issue 4 (27th January 2021) - Ramanauskaite, Ausra; Obreja, Karina; Sader, Robert; Becker, Jürgen; Schwarz, Frank
Abstract: Objectives: To evaluate peri‐implant tissue dimensions following nonsurgical (NS) and surgical therapy (S) employing different decontamination protocols of advanced ligature‐induced peri‐implantitis in dogs. Material & Methods: Peri‐implantitis defects ( n  = 5 dogs, n  = 30 implants) were randomly and equally allocated in a split‐mouth design to NS or S treatment using either an Er:YAG laser (ERL), an ultrasonic device (VUS), or plastic curettes + local application of metronidazole gel (PCM), respectively. Horizontal bone thickness (hBT) and soft tissue thickness (hMT) were measured at different reference points: (v0) at the marginal portion of the peri‐implant mucosa (PM); (v1) at 50% of the distance from PM to bone crest (BC); (v2) at the BC; (v3) at the most coronal extension of the bone‐to‐implant contact. Vertical peri‐implant tissue height was calculated from PM to BC. Results: All of the treatment groups showed a gradual hMT increase from v0 to the v2 reference point, followed by a reduction from v2 to the v3 region. The S‐VUS subgroup tended to be associated with higher hMT values at the v0 region than the NS‐VUS subgroup (0.44 mm versus 0.31 mm). PM‐BC distance varied from 2.22 to 2.83 mm in the NS group, and from 2.07 to 2.38 in the S group. Conclusion: Vertical and horizontal peri‐implant tissue dimensions were similar in different treatment groups.